Profil melayu Sambas dalam konteks asal-usul, tradisi dan budaya di Kalimantan Barat - Mardiyanti, Lisa Ranti; Ramadhan, Iwan; Kurnia, Heri (CV. Kurnia Grup, 2023)
The Sambas Malay Community is a group of indigenous people from West Kalimantan who inhabit most of the Sambas Regency, Bengkayang Regency and Singkawang City. Sambas Malay culture has its roots since the founding of the Sambas Sultanate, similar to other Islamic kingdoms in Kalimantan which are also included in the Malay group. This article uses a literature study method with the aim of investigating the development of the Malay ethnic group in West Kalimantan. Kinship relations among the Sambas Malay community in West Kalimantan are greatly influenced by factors such as location of residence, communication, emotional aspects, and so on. Most of the Malay Sambas people in West Kalimantan have a variety of livelihoods, one of which is rice farming. In some areas of Sambas, the Malay population of Sambas depends on rice farming as the main source of income for their families. Customs and culture in the Sambas Malay ethnic community in West Kalimantan include various traditions such as betangas, plain flour, bepapas, antar ajong, and so on.